Sonographic evaluation of epidural and intrathecal injections in cats. (November 2016) - Otero, Pablo E; Verdier, Natali; Zaccagnini, Andrea S; Fuensalida, Santiago E; Sclocco, Matias; Portela, Diego A; Waxman, Samanta
Abstract: Objectives: To describe the ultrasonographic anatomy of the caudal lumbar spine in cats and to detect ultrasound (US) signs associated with epidural or intrathecal injection. Study design: Prospective, clinical study. Animals: Twenty‐six client‐owned cats. Methods: Transverse (position 1) and parasagittal (position 2) two‐dimensional US scanning was performed over the caudal lumbar spine in all cats. Midline distances between the identified structures were measured. Cats assigned to epidural injection (group E, n  = 16) were administered a bupivacaine–morphine combination confirmed by electrical stimulation. Cats assigned to intrathecal injection (group I, n  = 10) were administered a morphine–iohexol combination injected at the lumbosacral level and confirmed by lateral radiography. The total volume injected (0.3 mL kg −1 ) was divided into two equal aliquots that were injected without needle repositioning, with the US probe in positions 1 and 2, respectively. The presence or absence of a burst of color [color flow Doppler test (CFDT)], dural sac collapse and epidural space enlargement were registered during and after both injections. Results: US scanning allowed measurement of the distances between the highly visible structures inside the spinal canal. CFDT was positive for all animals in group E. In group I, intrathecal injection was confirmed in only two animals, for which the CFDT was negative; seven cats inadvertently and simultaneously were administered an epidural injection and showed a positive CFDT during the second aliquot injection, and the remaining animal was administered epidural anesthesia and was excluded from the CFDT data analysis. Dural sac collapse and epidural space enlargement were present in all animals in which an epidural injection was confirmed. Conclusions and clinical relevance: US examination allowed an anatomical description of the caudal lumbar spine and real‐time confirmation of epidural injection by observation of a positive CFDT, dural sac collapse and epidural space enlargement.